Detection of microbial contamination of Salmonella in fodder and imported food that available in poultry fields and local markets - Doaa Adel Qasim, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This research was conducted to investigate the presence of Salmonella bacteria in animal production foods circulating in Baghdad markets, fish, imported feeds, and local meat chicken fields, A total of 270 food samples were collected, bacteriological and serological tests were conducted to diagnose salmonella and the results showed that 79 Salmonella isolates were isolated from a total of 270 chicken meat and feed samples, 37 isolates from chicken meat and its products, at a rate of 24.6%, in which eleven species of Salmonella bacteria were diagnosed, as they formed S.typhi of (13.51%), the percentage of S. typhimurium, S. anatum, S. gallinarinm and S. living stone was 8.1%, while the percentage of S. enteritidis, S. menston, S. menchen and S . ohio was 10.81%, the percentage of S. blokly and S. thompson was 5.4%. and 16 isolates of Salmonella bacteria were isolated, at a rate of 24.6%, out of the total of 60 samples obtained from fish and poultry feed in which eight species of Salmonella bacteria were diagnosed, as they formed S. ohio of (25%) while the other salmonella species of S. Dublin and S. thompson of (18.75%), and the percentage of other species of S. typhimurium, S. enteritidis, S. menston and S . hadar was 6.25%, while the percentage of S. braendrup was 12.5%. This confirms the existence of risks to public health and animal health as a result of the consumption of contaminated food and the use of contaminated feed in chicken farming fields.